Epoxidation of (E,E)-cinnamylideneacetophenones with hydrogen peroxide and iodosylbenzene with salen-mnIII as the catalyst - Santos, Clementina M.M. (2007)
(E,E)-Cinnamylideneacetophenones 3a–j were epoxidized under mild conditions with Jacobsen’s catalyst 4 and hydrogen peroxide or iodosylbenzene as oxidants. γ,δ-Monoepoxides and a diastereomeric mixture of α,β:γ,δ-diepoxides were obtained in each case, and only the α,β-monoepoxide of 4- nitrocinnamylideneacetophenone (3d) was isolated. The presence of a methyl group in the vinylic moiety of substrates 3i,j allowed the formation of two γ,δ-monoepoxide diastereomers. The epoxidation of (E,E)-2 -hydroxycinnamylid- Introduction Salen MnIII complexes are efficient catalysts for the epoxidation of various olefinic compounds.[1–3] Since the pioneering work of Kochi et al.,[4] many contributors have reviewed a wide range of applications of these powerful and selective catalysts.[5–7] Several oxidants have been used as effective oxygen donors in these epoxidations, with iodosylbenzene[ 8–11] and sodium hypochlorite[12–14] being the most frequently reported. Among other common olefin oxidants hydrogen peroxide,[15–17] oxone®,[18] dimethyldioxirane (DMD),[19–23] m-chloroperbenzoic acid (MCPBA),[24] molecular oxygen[25] and more recently also tetrabutylammonium monosulfate[24,26,27] and tetrabutylammonium periodate[ 28] have been used. Alkene epoxidation can also be achieved with simple co-catalysts such as imidazoles, pyridines and tertiary amine N-oxides, which act as axial ligands and, in some cases, as phase-transfer catalysts.[29–31] [a] Department of Agro-Industries, Escola Superior Agrária de Bragança, 5301-855 Bragança, Portugal Fax: +351-273-325405 E-mail: clems@ipb.pt [b] Department of Chemistry, University of Aveiro, 3810-193 Aveiro, Portugal Fax: +351-234-370084 E-mail: arturs@dq.ua.pt [c] Department of Organic Chemistry, University of Debrecen, 4010 Debrecen, Hungary Fax: +36-52-453836 E-mail: alevai@puma.unideb.hu Eur. J. Org. Chem. 2007, 2877–2887 © 2007 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim 2877 eneacetophenones 3h,j led to the formation of the corresponding γ,δ-monoepoxides as well as (E)-2,3-trans-3-hydroxy- 2-styryl-4-chromanones, which originated from the in situ cyclisation of 2,3-epoxy-1-(2-hydroxyphenyl)-5-phenyl- 4-penten-1-ones. The structures of all new compounds and the stereochemistry of the mono- and diepoxide diastereomers were established by NMR studies.